2014
DOI: 10.1038/srep06553
|View full text |Cite
|
Sign up to set email alerts
|

Introduction of impermeable actin-staining molecules to mammalian cells by optoporation

Abstract: The selective insertion of foreign materials, such as fluorescent markers or plasmids, into living cells has been a challenging problem in cell biology due to the cell membrane's selective permeability. However, it is often necessary that researchers insert such materials into cells for various dynamical and/or drug delivery studies. This problem becomes even more challenging if the study is to be limited to specific cells within a larger population, since other transfection methods, such as viral transfection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 36 publications
(43 reference statements)
1
24
0
1
Order By: Relevance
“…Targeted laser-assisted transfection of single opsins To achieve the targeted transfection of cells with opsin-encoding plasmids (ChR2 and ReaChR), we used optimized laser parameters 23 for optoporation into HEK293 cells. Before optoporation, the extracellular medium was exchanged with new DMEM medium-containing DNA plasmids (ReaChR or ChR2) with a final concentration of 1 mg mL 21 and incubated for 30 min.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Targeted laser-assisted transfection of single opsins To achieve the targeted transfection of cells with opsin-encoding plasmids (ChR2 and ReaChR), we used optimized laser parameters 23 for optoporation into HEK293 cells. Before optoporation, the extracellular medium was exchanged with new DMEM medium-containing DNA plasmids (ReaChR or ChR2) with a final concentration of 1 mg mL 21 and incubated for 30 min.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, there has been considerable interest in the optical transfection of cells using ultrafast pulsed light [15][16][17][18][19][20][21][22][23] because this approach offers selective targeting and higher efficiency and viability (.90% reported in vitro 22 ) than other methods. Furthermore, femtosecond (fs) near-infrared (NIR) laser-based transfection has been shown to be safe, resulting in high efficiency and high survival rates (93%) of optoporated embryos during development 20 , as well as suitable for in vivo gene delivery 24 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5] Cell membrane perforation by focused femtosecond laser pulses provides an exclusive technology to introduce external molecules into a single cell, i.e., optoinjection, without significant cell damage because of a nonlinear interaction in a tiny focused spot. [6][7][8][9] Recently, the use of nanoparticles or microparticles has been accelerating attractive achievements to expand the capability of ultrashort laser optoinjection technology toward simultaneous treatment of multiple cells. Chakravarty et al 10 reported the delivery of DNA, protein, and fluorescence molecules into cells in a cuvette by using carbon black nanoparticles and a femtosecond laser.…”
mentioning
confidence: 99%
“…In recent years, cellular imaging by direct laser photoporation for delivery of dyes into live cells is being explored as a new and promising application. In particular, fs laser-assisted direct photoporation was used to deliver actin-staining fluorophores into rat cortical neurons for visualizing the cytoskeleton of dendrites [159].…”
Section: Direct Laser Photoporationmentioning
confidence: 99%